"Museum spaces in post-apartheid South Africa": the Durban Art Gallery as a case study - Brown, Carol (Rhodes University, Faculty of Humanities, Department of Fine Art, 2006)
This dissertation examines the history of the Durban Art Gallery from its founding in 1892 until 2004, a decade after the First Democratic Election. While the emphasis is on significant changes that were introduced in the post-1994 period, the earlier section of the study locates these initiatives within a broad historical framework. The collecting policies of the museum as well as its exhibitions and programmes are considered in the light of the institution 's changing social and political context as well as shifting imperatives within a local, regional and national art world. The Durban Art Gallery was established in order to promote a European, and particularly British, culture, and the acquisition and appreciation of art was considered an important element in the formation of a stable society. By providing a broad overview of the early years of the gallery, I identify reasons for the choice of acquisitions and explore the impact and reception of a selection of exhibitions. I investigate changes during the 1960s and 1970s through an examination of the Art South Africa Today exhibitions: in addition to opening up institutional spaces to a racially mixed community, these exhibitions marked the beginning of an imperative to show protest art. I argue that, during the political climate of the 1980s, there was a tension in the cultural arena between, on the one hand, a motivation to retain a Western ideal of 'high art' and, on the other, a drive to accommodate the new forms of people's art and to challenge the values and ideological standpoints that had been instrumental in shaping collecting and exhibiting policies in the South African art arena. I explore this tension through a discussion of the Cape Town Triennial exhibitions, organised jointly by all the official museums, which ran alongside more inclusive and independently curated exhibitions, such as Tributaries, which were shown mainly outside the country. The post-1994 period marked an opening up of spaces, both literally and conceptually. This openness was manifest in the revised strategies that were introduced to show the Durban Art Gallery 's permanent collection as well as in two key public projects that were started - Red Eye @rt and the AIDS 2000 ribbon. Through an examination of these strategies and initiatives, I argue that the central role of the Durban Art Gallery has shifted from being a repository to providing an interactive public space.
Keywords: Durban Art Gallery -- History; Museums -- South Africa -- Durban; Art museums -- South Africa -- Durban; Art -- South Africa -- Durban -- Exhibitions; Art, Modern -- 20th century -- Exhibitions; Art, Modern -- 19th century -- Exhibitions